Prevalence of Teenage Pregnancy & Its Outcome at Shaikh Zaid Women Hospital Larkana - Sumera Brohi, Shazia Ahmed Jatoi, Saeed U Nisa Sangi, Shaista Tabasum Abro, Rukhsana Shaikh, Ayesha Jalbani (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Teenage adolescent pregnancy is an important community health issue globally. Research shows that mothers in teenage period are at a higher risk of maternal death and complications related with pregnancy in comparison to the mothers who are adult. Therefore, this research was directed to examine the sociodemographic profile and fetal and maternal outcomes related with teenage pregnancy and their comparison with mothers of 20-30 years of age. Study Design: A comparative cross-sectional study. Place and Duration: In the obstetrics and Gynecology department of Sheikh Zaid Women Hospital Larkana for one-year duration from March 2021 to February 2022. Methods: A total of 60 teenage mothers ≤19 and 60 mothers who were 20-30 years of age respectively, were nominated as controls and cases. Data on the obstetric complications, fetal outcomes and sociodemographic profile were collected through face-to-face interviews using a pre-tested, pre-designed, partially structured questionnaire. The statistics were analyzed by entering data in the excel sheet of Microsoft. Results: In this study, 18.1 years was the mean age in teenage pregnant females and 24.3 years in the control group. 17.8 years was the mean age at which teenage mothers were married and for adults it was 20.1 years. 66.7% of teenage mothers and 61.7% of the control group are of high-low socioeconomic status. 80% of teenage pregnant females and 75% of control group were from rural areas. The mainstream of teenage mothers (70%) and control mothers (58.3%) are housewives by profession. The consanguineous marriages were observed in 33.3% of adolescent pregnant females and 41.7% in the control group. In this study, 38.3% and 46.7% of the mothers in adolescent and control group respectively had ante-natal checks during their pregnancy. Stillbirth / miscarriage were reported in 13.3% of adolescent mothers and 25% in the control group. 63.3% of teenage mothers had mild anemia and 53.3% in controls. The incidence of malnutrition (40% vs 15%, p <0.05), PPH (25% vs 6.7%, p <0.05), PROM (20% vs 3.3%, p <0.05) was significant in teenage mothers in comparison to mothers who were adults. The incidence of PIH was lower significantly in mothers during adolescence in comparison to adult mothers (13.3% vs. 31.7%, p <0.05). Conclusions: Complications such as PROM, maternal malnutrition, premature delivery, PPH and low birth weight occurred more frequently in adolescent mothers than in mothers who were adults. The adult mother’s higher proportion of PIH than in teenage mothers. Keywords: Adult pregnancy, teenage pregnancy, sociodemographic factors, adverse fetal and maternal outcomes.